The Active Role of Admin strative Skills in Reinforcing Strategic Entrepreneur Ship Through Organizational Flexibility: دراسة استطلاعية لأراء عينة من الإدارات العليا والوسطى في المصارف العراقية الخاصة / بغداد (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The study has tackled three important variables on the strategic and organizational level, that are : (Administrative skill, strategic Entrepreneurship  and organizational flexibility). Through the statistical analysis is, the research hers have sought to identify the relation among them. The study has been applied on a sample of (44) private banks in Iraq. A questionnaire, which has been designed according to a number of international standards, has been used. It's made of (29) items that cover the three variables to test their hypotheses. A number of statistical tools have been used A number of conclusion have been reached and recommendations have also been suggested.